2022
DOI: 10.1002/mp.15669
|View full text |Cite
|
Sign up to set email alerts
|

Improved resolution of D‐bar images of ventilation using a Schur complement property and an anatomical atlas

Abstract: Background: Electrical impedance tomography (EIT) is a nonionizing imaging technique for real-time imaging of ventilation of patients with respiratory distress. Cross-sectional dynamic images are formed by reconstructing the conductivity distribution from measured voltage data arising from applied alternating currents on electrodes placed circumferentially around the chest. Since the conductivity of lung tissue depends on air content, blood flow, and the presence of pathology, the dynamic images provide region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…In this study, corresponding EIT image sequences were obtained during apnoea using beat-tobeat perfusion and hypertonic saline perfusion, respectively, and we found that changes in beat-tobeat perfusion before and after embolisation were reflected in both end-expiratory and endinspiratory pauses. In addition, the selection of appropriate animal models is important for obtaining reliable and meaningful experimental results [29,30]. As we know, porcine models are the basis for preclinical and translational studies of many diseases treatments [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, corresponding EIT image sequences were obtained during apnoea using beat-tobeat perfusion and hypertonic saline perfusion, respectively, and we found that changes in beat-tobeat perfusion before and after embolisation were reflected in both end-expiratory and endinspiratory pauses. In addition, the selection of appropriate animal models is important for obtaining reliable and meaningful experimental results [29,30]. As we know, porcine models are the basis for preclinical and translational studies of many diseases treatments [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A novel method to quantitatively measure the image quality of 2-D EIT images when a CT scan is available was proposed in [44]. The method uses the structural similarity index (SSIM) [52] or the multiscale structural similarity index (MS-SSIM) [53] to compare to ground truth images that are derived from the CT scans, since direct comparison between EIT images of conductivity and CT images of tissue density would be incorrect due to the differences between the two modalities.…”
Section: Image Quality Evaluationmentioning
confidence: 99%
“…The method uses the structural similarity index (SSIM) [52] or the multiscale structural similarity index (MS-SSIM) [53] to compare to ground truth images that are derived from the CT scans, since direct comparison between EIT images of conductivity and CT images of tissue density would be incorrect due to the differences between the two modalities. The reader is referred to [44] for details of the construction of the ground truth images. Briefly, inspiratory and expiratory CT scans are registered and rescaled, and then segmented to identify the lung region.…”
Section: Image Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation